Torah old and new : exegesis, intertextuality, and hermeneutics - Witherington, Ben, III, 1951- (Project Muse, 2018)
Reading the books of the Law, the Pentateuch, in their original context is the crucial prerequisite for reading their citation and use in later interpretation, including the New Testament writings, argues Ben Witherington III. Here, he offers pastors, teachers, and students an accessible commentary on the Pentateuch, as well as a reasoned consideration of how these books were heard and read in early Christianity. By reading "forward and backward," Witherington advances the scholarly discussion of intertextuality and opens a new avenue for biblical theology.